SCHOOL ORGANIZATIONAL CONFLICT MANAGEMENT IN NIGERIA - Adeyemi, Yusuf Lateef (Sokoto Educational Review, 2018)
The paper considers school organizational conflict management as one of the contemporary issues in educational management in Nigeria. The paper examines the nature, concept, causes and consequences of school organizational conflict in Nigeria schools. Conflict as an interactive process manifests in incompatibility, disagreement, or difference within or between social entities (i.e individuals, groups, organizations, e.t.c). The paper establishes the inevitability of conflict. While a degree of it serves as stimulus to creativity and vitality for individuals and organizational growth, unresolved conflict could be dysfunctional. Thus, it views conflict management as a situational approach, because either too much or too little conflict can be dysfunctional for an organization. The secret to successful conflict management is to use an appropriate strategy at the appropriate time. The paper considers three viable conflict management strategies that could be adopted by school manager as a tool towards enhancing school organizational performance as follows: stimulating conflict for constructive end; controlling conflict before it gets out of hand and resolving or eliminating conflict if it does.